2020
DOI: 10.1186/s13011-020-00287-1
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorders and the risk of progression of liver disease in people with hepatitis C virus infection – a systematic review

Abstract: Liver cirrhosis and other chronic liver diseases are usually compartmentalized into separate categories based on etiology (e.g., due to alcohol, virus infection, etc.), but it is important to study the intersection of, and possible interactions between, risk factors. The aim of this study is to summarize evidence on the association between alcohol use disorders (AUDs) and decompensated liver cirrhosis and other complications in patients with chronic Hepatitis C virus (HCV) infection. A systematic search of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…Consistent with previous research, we found that unhealthy alcohol use 9 and social condition proxies 35 – expressed in our study by unemployment and a low educational level – were also significant independent predictors of severe fibrosis. This suggests that negative social conditions, as well as current or past unhealthy alcohol use, constitute missed opportunities for prompt HCV screening and referral for HCV care, resulting in more advanced liver disease by the time treatment is initiated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous research, we found that unhealthy alcohol use 9 and social condition proxies 35 – expressed in our study by unemployment and a low educational level – were also significant independent predictors of severe fibrosis. This suggests that negative social conditions, as well as current or past unhealthy alcohol use, constitute missed opportunities for prompt HCV screening and referral for HCV care, resulting in more advanced liver disease by the time treatment is initiated.…”
Section: Discussionsupporting
confidence: 92%
“…Among these, coffee consumption and alcohol abstinence or very low alcohol consumption are known to have anti-inflammatory effects and/or anti-fibrotic properties. 8 Although the effects of unhealthy alcohol use on liver fibrosis are widely documented in people living with HCV, 9 results showing its effect on liver fibrosis after HCV cure in the DAA era are lacking. With regard to coffee, elevated consumption was recently associated with slower liver disease progression (including reduced hepatocellular carcinoma (HCC) incidence in patients with hepatitis C, alcohol-related liver disease, or non-alcoholic fatty liver disease 10 , 11 ) and with reduced mortality (in HIV-HCV co-infected patients).…”
Section: Introductionmentioning
confidence: 99%
“…Data from 286641 people with chronic HCV infections, of whom 22.3% with AUDs, showed that AUD diagnosis was associated with a 3.3-fold risk for progression of liver disease. Almost 4 out of 10 decompensated liver cirrhosis cases were attributable to an AUD[ 217 ]. Interestingly, similar findings were reported in a very recent study on the effects of alcohol in patients with HBV[ 218 ].…”
Section: Effect Of Alcohol Consumption In Hcv-related Fibrosis and Ci...mentioning
confidence: 99%
“…40,41 Though studies show that the highest absolute rate of disease in homeless individuals is for hepatitis C, 7,42,43 it is imperative that alcohol use be concurrently addressed. Alcohol acts synergistically with HCV resulting in a more than three-fold higher risk for liver disease progression, 39 maybe by enhancing HCV replication. 44 In our study, alcohol use was an independent predictor Abbreviations: ccCK, caspase-cleaved cytokeratin; HA, Hyaluronic acid; IFNγ, interferon-gamma; IL, interleukin; MMP2, Matrix metalloproteinase-2; PIINP, Procollagen III amino terminal peptide; TIMP-1, Tissue inhibitor of metalloproteinase-1; TNFα, tumour necrosis factor alpha.…”
Section: Discussionmentioning
confidence: 99%